Effects of elevated carbon dioxide on plant growth and leaf photosynthesis of annual ryegrass along a phosphorus deficiency gradient - Li, Fei; He, Chunlin; Chang, Zhijie; Ma, Chao; Yu, Jingjin; Liu, Liang; Zhang, Yunxin; Hao, Lihua (Frontiers in Plant Science, 2023)
Soil phosphorus (P) deficiency limits plant growth and productivity in grassland ecosystems and may moderate the growth-promoting effects of "carbon dioxide (CO2) fertilization effect". To evaluate the interactive effects of these two factors on the growth and physiology for annual ryegrass (Lolium multiflorum Lam.), plants were grown in controlled growth chambers with a range of P supply (0.004, 0.012, 0.02, 0.06, 0.1 and 0.5 mM) under two levels of CO2 (400 and 800 μmol mol -1 , respectively). Elevated [CO2] dramatically increased the aboveground biomass and net photosynthetic rates of annual ryegrass by 14.5% and 25.3% under sufficient P supply (0.5 mM), respectively, whereas decreased the belowground biomass and net photosynthetic rates under lower P supply of P0.004, P0.02, and P0.06. Two-way ANOVA results showed that CO2 × P (p < 0.001) significantly affected stomatal traits, leaf photosynthesis and biomass. The stimulation of growth and photosynthesis by elevated CO2 concentration (e[CO2]) was reduced or highly suppressed, indicating that the sensitivity of annual ryegrass to P deficiency was enhanced under e[CO2]. These results indicated that P limitation may offset the positive effects of e[CO2] on plant growth by altering stomatal traits, leaf photochemical processes and biochemical composition in annual ryegrass.